Downregulation of CCKBR Expression Inhibits the Proliferation of Gastric Cancer Cells, Revealing a Potential Target for Immunotoxin Therapy - Li, Meng; Chang, Jiang; Ren, Honglin; Song, Defeng; Guo, Jian; Peng, Lixiong; Zhou, Xiaoshi; Zhao, Ke; Lu, Shiying; Liu, Zengshan; Hu, Pan (Current Cancer Drug Targets, 2022)
Background: Increased CCKBR expression density or frequency has been reported in many neoplasms. Objective: We aimed to investigate whether CCKBR drives the growth of gastric cancer (GC) and its potential as a therapeutic target of immunotoxins. Methods: A lentiviral interference system was used to generate CCKBR-knockdown gastric cancer cells. Cell Counting Kit-8 and clonogenic assays were used to evaluate cell proliferation. Woundhealing and cell invasion assays were performed to evaluate cell mobility. Cell cycle was analyzed by flow cytometry. Tumor growth in vivo was investigated using a heterologous tumor transplantation model in nude mice. In addition, we generated the immunotoxin FQ17P and evaluated the combining capacity and tumor cytotoxicity of FQ17P in vitro. Results: Stable downregulation of CCKBR expression resulted in reduced proliferation, migration and invasion of BGC-823 and SGC-7901 cells. The impact of CCKBR on gastric cancer cells was further verified through CCKBR overexpression studies. Downregulation of CCKBR expression also inhibited the growth of gastric tumors in vivo. Furthermore, FQ17P killed CCKBR-overexpressing GC cells by specifically binding to CCKBR on the tumor cell surface. Conclusion: The CCKBR protein drives the growth, migration, and invasion of gastric cancer cells, and it might be a promising target for immunotoxin therapy based on its aberrant expression, functional binding interactions with gastrin, and subsequent internalization.
Keywords: immunotoxin